Envolvimento dos sistemas serotoninérgico, GABAérgico e glutamatérgico no córtex cingulado anterior na ansiedade-traço e -estado de ratos Wistar adultos - Souza, Thiago Henrique Almeida (2021)
The high prevalence of anxiety as a disorder and its important socioeconomic impact in the world has been highlighted. Furthermore, its neurobiology is still a challenge. In recent decades, the neural circuitry involved in the state anxiety has been identified. State anxiety is the anxiety a subject experiences when faced with a threatening stimulus at a particular moment in time. However, little is known about trait anxiety, a relatively stable personality trait and a predisposing factor for anxiety disorders. The brain structure that has been related to the anxious trait is the medial prefrontal cortex. However, few studies show differentiation of roles of their subnuclei, so that the anterior cingulate cortex (ACC) would be involved with the trait. Thus, knowing that neurotransmitters such as serotonin, gamma aminobutyric acid (GABA) and glutamate are involved in anxiety, the present study investigated the participation of these neurotransmitter systems in ACC in the trait anxiety of adult Wistar rats. As, by definition, trait anxiety modulates state anxiety, this was also evaluated. For the behavioral assessment, three animal models were used: 1) Free Exploratory Paradigm (FEP), animal model of trait anxiety; 2) Hole board (HB); and 3) Elevated plus maze (EPM), state anxiety models. Initially, the animals were categorized according to their trait anxiety levels (high, low and medium) (FEP1) and allocated to experiments. Exp I used high; Exp II used low; Exp III used medium trait anxiety animals. The animals were again submitted to FEP (FEP2) and HB, and before each behavioral assessment were administered in ACC drugs that increased or decreased serotonergic (Fluoxetine or WAY-100635), GABAergic (Muscimol or Bicuculline) and glutamatergic (NMDA or Ketamine) and their respective controls. Moreover, in Exp IV, all animals from previous experiments were submitted to EPM, and evaluated without taking into account trait anxiety levels. At the end of the experiments, the histological analysis of the drug administration site was performed. All data were analyzed using analysis of variance and a posteriori Tukey test. The results of the present study showed that, in Exp I, the modulation of the serotonergic, GABAergic and glutamatergic systems in the ACC decreased trait anxiety in highly anxious rats, while by submitting the animals to HB, the administration of Fluoxetine increased state anxiety. In Exp II, the modulation of all systems increased trait anxiety in rats with low trait anxiety, whereas, in HB, state anxiety levels were increased with the administration of NMDA. In Exp III, only the modulation of the glutamatergic system, with NMDA, increased both trait and state anxiety levels. However, none of the evaluated neurotransmitter systems altered the state anxiety modeled in the EPM. Thus, the present study showed, for the first time, the participation of the serotonergic, GABAergic and glutamatergic systems in the ACC in the trait anxiety of Wistar rats with different levels of anxiety. Furthermore, we showed that ACC is also involved with the modulation of the state anxiety.